The Correlation Between Reading Fluency and Students' Reading Comprehension in Junior High School - Indira Dyah Prameswari; Suvi Akhiriyah (Jetlal, 2023)
Reading comprehension is the ability to comprehend the text. One of the factors that may affect it is reading fluency. Readers who can identify the words accurately and automatically may help to focus most of their attention on reading comprehension. Therefore, this study investigated the correlation between reading fluency and students’ reading comprehension. This research used 64 7th-grade students as participants. Two instruments were used; a reading fluency test (CBM) and a reading comprehension test. This study showed 41 students were categorized as high risk (64%) in reading fluency. In reading comprehension, 27 students scored 56 – 70 (M = 60.0781), meaning that most students’ reading comprehension skills were moderate. Then, the result of Pearson Product Moment showed that there is no relationship between reading fluency and students’ reading comprehension at the Junior High School level (p–value = 0.102) since students are still trying to improve their reading skills. Then, students may feel anxiety about doing oral performance.